Challenge Based Learning as authentic learning environment for STEM identity construction - Taconis, Ruurd; Bekker, Tilde (Frontiers in Education, 2023)
Engineering education more and more adopts Challenge Based Learning. In CBL, students learn in groups by taking on open and challenging projects that draw on a broader STEM knowledge base. The challenges reflect and mimic STEM professional core practices (e.g. higher education) or authentic but pedagogically simplified versions (e.g. secondary education). Challenges also connect to societally relevant themes and issues. CBL thus seems well suited to helping students build a positive STEM identity (seeing oneself and being recognized by others as a STEM person c.q., STEM professional). However, CBL is a very new educational concept with little empirical research yet available. Therefore, this paper explores the question of CBL's contribution to STEM identity development at a conceptual level. What, conceptually, can CBL be expected to contribute to STEM identity development?We first explore the concept of CBL as it is currently defined to find its strengths and weaknesses and improve it. We then look for empirical evidence on the effects of conceptually akin education (such as Design-Based Learning and Project-Based Learning) on STEM identities. When learning effects can be traced using educational theories to conceptual features they share with CBL, these can be building blocks for our modelling of CBL's contribution to the development of STEM identities.Current definitions of CBL were found to be purely enumerative and did not clearly distinguish CBL from related concepts such as Problem Based Learning (PBL) or Design Based Learning (DBL). A new definition for CBL is proposed that is based on an underlying pedagogical vision.It is concluded that CBL and related forms of education can be expected to facilitate the construction of STEM identities. Primarily through a combination of a motivation boost, a higher perception of competence and the CBL and STEM identity construction 2 enjoyable and experiential orientation to STEM that it provides students. However, CBL seems limited with respect to the development of STEM identities in vocational or higher education.